Antimicrobial effects of grapefruit seed extract microfibers against mouse hepatitis virus, Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa (Journal of Laboratory Animal Science, 2024)
Grapefruit seed extract (GSE), which contains flavonoids, possesses antibacterial, antiviral, and antifungal properties. This  study investigated the antimicrobial activity of cellulose-bound GSE microfibers against mouse hepatitis virus (MHV)  for three weeks and against Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa for one week. The  disinfectant was smeared on a petri dish to inactivate the MHV for three weeks or to prevent the growth of the selected  bacteria for one week. As the disinfectant effect lasted at least one week, GSE microfibers could have applications in  disinfecting laboratory animal facilities. The virus or bacteria mixed with the disinfectant did not cause cytopathic effects  in the cells or growth on the media after one week.
Keywords: Antimicrobial; disinfectant; grapefruit seed extract; microfiber